Creative Thinking Skills: Project Based Learning (PjBL) in the Media and Learning Resources Development Course - Safarati, Nanda; Zuhra, Fatma; Liani, Novi Sari (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
This study uniquely explores the enhancement of students' creative thinking skills through the application of Project-Based Learning (PjBL) in media and learning resource development courses, addressing a critical gap in contemporary educational methodologies. The research employed a quasi-experimental design at Almuslim University within the Basic Education Study Program (PGSD). The sample included 3rd semester PGSD students, with 29 students in the experimental group (class 3f) and 29 in the control group (class 3e), selected using purposive sampling. Utilizing a Posttest Only Control design, data were collected through observation and tests. Validity was ensured through content and empirical checks, and data analysis involved normality, homogeneity tests, and hypothesis testing using SPSS 23.0 software. The findings indicate a significant improvement in students' creative thinking skills as a result of implementing the PjBL model in media and learning resource development courses. The experimental group demonstrated enhanced critical thinking, creativity, and problem-solving abilities compared to the control group. These results underscore the efficacy of PjBL in fostering essential 21st-century skills among students. The structured, hands-on approach of PjBL not only engages students actively but also encourages collaborative learning and innovative thinking. The application of PjBL in media and learning resource development courses significantly enhances students' creative thinking skills. This study's implications extend to broader educational contexts, suggesting that integrating PjBL can effectively prepare students for future challenges by promoting critical, creative, and collaborative skills essential for success in a rapidly evolving world.